Anthropic influences on the sedimentation rates of lakes situated in different geographic areas. (July 2017) - Simon, Hedvig; Kelemen, Szabolcs; Begy, Róbert-Csaba
Abstract: The aim of this study is to determine the effects of natural and anthropic events occurring in the last 30 years in the catchment areas of four Romanian lakes (St. Anna Lake, Red Lake, Vârşolţ Lake and Matiţa Lake) originating from four different geomorphologic areas. A total of eleven sediment cores have been processed for age and sedimentation rate determination using the 210 Pb dating method. Total 210 Pb was measured via alpha spectrometry by 210 Po using PIPS detectors, while supported 210 Pb was measured by 226 Ra using HPGe detectors. Ages and sedimentation rates were calculated using the CRS model. The values of the sedimentation rates have grown multiply in the last three decades: 2.66 times in case of the St. Anna Lake (from 0.06 ± 0.01 g/cm 2 y to 0.16 ± 0.02 g/cm 2 y), up to 6.72 times in case of Red Lake (0.36 ± 0.04 g/cm 2 y to 2.42 ± 0.36 g/cm 2 y), 4.02 times in case of Vârşolţ Lake (04 g/cm 2 y to 1.53 ± 0.18 g/cm 2 y) and up to 16.18 times in case of Matiţa Lake (0.27 ± 0.03 g/cm 2 y to 4.37 ± 0.32). Highlights: Sedimentation rates for the last 30 years of four Romanian lakes were compared. Gamma spectrometric measurements were carried out for 210 Pb, 226 Ra and 137 Cs. Alpha spectrometry was used for the determination of 210 Po. Sedimentation rates increased 2.66 times for St. Anna, 6.72 times for Red, 4.02 times for Vârşolţ, 16.18 times for Matiţa. These increases are caused by anthropic events (mainly deforestation) in case of the Red Lake and St. Anna Lake. And natural factors, such as the increasing of the regional precipitation, in case of the Matiţa Lake and Vârşolţ Lake.